Numerical methods for solving inverse problems of mathematical physics - Samarskiĭ, A. A. (Aleksandr Andreevich) (Inverse and ill-posed problems series., 2007)
The main classes of inverse problems for equations of mathematical physics and their numerical solution methods are considered in this book which is intended for graduate students and experts in applied mathematics, computational mathematics, and mathematical modelling.